Sounding the alarm on leiomyosarcoma recurrence: role of circulating tumor DNA - Kasper, Bernd; Wilky, Breelyn A. (Clinical cancer research, 2022)
Recent work confirms a bench-to-bedside approach that circulating tumor DNA is associated with outcome and objective response to chemotherapy in patients with advanced leiomyosarcoma. Liquid biopsies may be used for risk stratification in future trials guiding treatment decisions by identifying patients who are likely to benefit from chemotherapy.See related article by Madanat-Harjuoja et al., p. 2579
Gesehen am 23.01.2024